La necesidad de garantizar el derecho de familia, dentro de las relaciones monogámicas de unión de hecho, por medio de la jurisdicción voluntaria, dada por la fe notarial - Granda., José Antonio (2015)
This thesis seeks to ensure agile and simple procedures for monogamous relationships such as the bonding company which actually does not own a rapid procedure on voluntary jurisdiction abalizado by notarial faith. in less time so it is necessary that the monogamous family rights are guaranteed, with less time and by the notarial faith. Our state guarantees acts and contracts through public faith, thus ensuring public safety justice without delay, so that the immediate effects produced against union recognition actually produce immediate effects on property. Law marriage as a monogamous way that is guaranteed by the state, so it is important to generate about the same agile and simple procedures that ensure its constitution in less time, and its legal effects that it produces. The notarial faith is a way to formalize the acts that occur within the voluntary jurisdiction, the same that is given by a public document, which is notarized by notary faith is important that systems are developed for the different forms monogamous family to ensure the same quick and agile constitution.